This Thing of Ours - Joseph, Frederick ([Place of publication not identified] : Candlewick Press (MA), 2025)
"In an instant, Ossie Brown's entire future is in jeopardy when a torn ACL ends his promising basketball career. Now that basketball is no longer a major part of his identity, Ossie -- a Black teen who doesn't come from wealth and privilege -- must navigate his new place in the social and academic ecosystems of his affluent, predominantly white school. When a Black teacher encourages him to join her highly regarded writing program, Ossie begins to find a new purpose, buoyed by not only the rich works of literature by marginalized authors he's now reading, but also by new friends who see him as something more than an asset to the sports program. Everything changes when some students' viral 'anti-woke' video puts the teacher's job, the writing program, and even Ossie's friends' safety at risk -- and Ossie must find his true voice. This unflinching novel confronts critical issues like racism and classism, the treatment of student athletes, homophobia, and book banning while weaving together a moving testament to family, romance, friendship, and the power of words"--.
new ya book 2025 spring.
Keywords: Homophobia; Families; Teenagers; Prejudices; Classism; Students, Black; High school athletes